Using an integrative, Cognitive Analytical Therapy (CAT) approach to treat intimate partner violence risk - Tully, Ruth; Barrow, Alex (Emerald, 2017)
Aims: There is limited research on Cognitive Analytic Therapy (CAT) in forensic contexts; this case study therefore significantly contributes to the knowledge base. This case study presents the assessment and treatment of an adult male offender with a diagnosis of schizophrenia. The client’s offence involved intimate partner violence and was committed at a time of acute psychiatric relapse. Method: Twelve sessions of Cognitive Behavioural Therapy (CBT) and CAT informed treatment were individually designed to meet the needs of the client, delivered in an in-patient setting in the UK. The client’s progress was assessed using psychometric, observational, and narrative/descriptive methods. Results: Psychometric evidence was limited by distorted responding. However, narrative/descriptive assessment indicated that progress had been made in some areas. Recommendations for further treatment were made. Conclusions: Twelve sessions did not meet all of the client’s needs. The use of CAT as a model that his team could use in understanding his violence was conducive to risk management. Overall, insight gained through CAT based psychological intervention contributed to risk reduction. Originality: This case study demonstrates the applicability of CAT to forensic settings